Where Are Our ”Argo(t)nautes”? - Felix NICOLAU (ACROSS)
The problem of the contemporary writer is the range of his/her vocabulary and idiomatic phrases. In spite of the Romanian slang being so rich, the corresponding literature manifests a sort of deafness in this regard. There is an incapacity of capturing the spoken language at many writers as they are enclosed in tiny circles. The consequence is that the slang in many oeuvres is sketchy, unimaginative. If we look at the terms in G. Volceanov’s Dictionary of Argot, we perceive instantly the gap between trendy contemporary writers’ language and the language in use at the outskirts of society. The linguistic scarcity becomes more obvious with the forceful advent of political correctness. Writers seem to resort more and more to self-censorship.